Methodological Aspects of Implementation of the Safety System in the Activity of Hotel and Catering Industry Enterprises - Prokhorova, Viktoria; Davydova, Oksana; Protsenko, Valentina (International Journal of Engineering and Technology, 2018)
The essence of the HACCP system is revealed. The urgency of the development and implementation of the HACCP system in the hotel and catering business enterprises is proved either. The conceptual aspects of the HACCP methodology are presented that allows to maintain the focus on the safety and quality of the products and services of the hotel and catering industry as the highest priority. The successive stages of the HACCP system implementation in the hotel and catering business have been developed. The checklist for analyzing the risks of the process of reception and accommodation of the consumers at the hotel is presented either. It has been proved that the development and implementation of the HACCP system will provide the hotel and catering industry with the competitive advantages.Â Â Â
Keywords: Consumer; critical control point; hotel and catering economy; products; quality; risk; security; services; HACCP system